Penerapan Multiple Attribute Decision Making Menggunakan Weighting Product Untuk Pemilihan Laptop - Auliya Rahman Isnain (Journal of Artificial Intelligence and Technology Information (JAITI), 2026)
In the process of choosing a laptop, problems often arise in the form of numerous alternatives with varied specifications, complex differences in user needs, limited accurate information, as well as difficulties in comparing various criteria such as price, performance, battery life, and device quality, resulting in decision-making that is less objective, inconsistent, and potentially leads to suboptimal choices. The purpose of this study for the selection of laptops used is based on price, RAM, processor, storage and size in recommending laptops using the WP method. The results of the system recommendation assessment using applications and manual calculations provide recommendations for Microsoft Surface Pro 6 Laptop ranked first with a final score based on the WP method getting a result of 0, 274854256. The test results get a value of 100% according to the system functionality testing using blackbox testing. Based on the results of data processing of respondents' responses as many as 16 respondents based on 4 TRITAM Model criteria, Trust results were obtained (Trust) of 77.92%, Risk of Use (Risk) of 75.83%, Perceived Usefulness of 89.79%, Perception of Ease of Use (Perceived easy of Use) of 81.04%. The overall test results using the TRITAM Model for technology acceptance were Good at 82.56%.